Spectrum of Atypical Clinical Presentations in Patients with Biallelic PRF1 Missense Mutations. Issue 12 (16th July 2015) - Tesi, Bianca; Chiang, Samuel C. C.; El‐Ghoneimy, Dalia; Hussein, Ayad Ahmed; Langenskiöld, Cecilia; Wali, Rabia; Fadoo, Zehra; Silva, João Pinho; Lecumberri, Ramón; Unal, Sule; Nordenskjöld, Magnus; Bryceson, Yenan T.; et al.
<x xml:space="preserve">Abstract</x> Background Perforin, encoded by PRF1, is a pore‐forming protein crucial for lymphocyte cytotoxicity. Biallelic PRF1 nonsense mutations invariably result in early‐onset hemophagocytic lymphohistiocytosis (HLH), termed familial HLH type 2 (FHL2). In contrast, biallelic PRF1 missense mutations may give rise to later‐onset disease and more variable manifestations. Procedure We retrospectively searched our database for patients from families with siblings carrying biallelic PRF1 missense mutations where at least one sibling did not develop HLH, and for patients with biallelic PRF1 missense mutations and an atypical presentation of disease. We reviewed their clinical, genetic, and immunological characteristics. Results In all, we identified 10 such patients, including three sibling pairs with discordant manifestations. Interestingly, in two families, siblings of late‐onset HLH patients developed Hodgkin lymphoma but no HLH. In a third family, one sibling presented with recurrent HLH episodes, whereas the other remains healthy. Of note, the affected sibling also suffered from systemic lupus erythematosus. Additional unrelated patients with biallelic PRF1 missense mutations were affected by neurological disease without classical signs of HLH, gastrointestinal inflammation as initial presentation of disease, as well as a hematological malignancy. Compared to early‐onset FHL2 patients, the patients with an atypical presentation displayed a partial recovery of NK cell cytotoxicity upon IL‐2 stimulation in vitro. Conclusions Our findings substantiate and expand the spectrum of clinical presentations of perforin deficiency, linking PRF1 missense mutations to lymphoma susceptibility and highlighting clinical variability within families. PRF1 mutations should, therefore, be considered as a cause of several diseases disparate to HLH. Pediatr Blood Cancer © 2015 Wiley Periodicals, Inc.